Renal Tubular Dysfunction in Sickle Cell Disease - Geraldo B. Silva Junior; Ana Patrícia F. Vieira; Amanda X. Couto Bem; Marília P. Alves; Gdayllon C. Meneses; Alice M.C. Martins; Talita R. Sanches; Lúcia C. Andrade; Antonio C. Seguro; Alexandre B. Libório; Elizabeth F. Daher (Kidney & Blood Pressure Research, 2014)
Background/Aims: Kidney abnormalities are one of the main chronic complications of sickle cell disease (SCD). The aim of this study is to investigate the occurrence of renal tubular abnormalities among patients with SCD. Methods: This is a prospective study with 26 SCD adult patients in Brazil. Urinary acidification and concentration tests were performed using calcium chloride (CaCl2), after a 12h period of water and food deprivation. Fractional excretion of sodium (FENa), transtubular potassium gradient (TTKG) and solute free water reabsorption (TcH2O) were calculated. The SCD group was compared to a group of 15 healthy volunteers (control group). Results: Patient`s average age and gender were similar to controls. Urinary acidification deficit was found in 10 SCD patients (38.4%), who presented urinary pH >5.3 after CaCl2 test. Urinary osmolality was significantly lower in SCD patients (355±60 vs. 818±202mOsm/kg, p=0.0001, after 12h period water deprivation). Urinary concentration deficit was found in all SCD patients (100%). FENa was higher among SCD patients (0.75±0.3 vs. 0.55±0.2%, p=0.02). The TTKG was higher in SCD patients (5.5±2.5 vs. 3.0±1.5, p=0.001), and TcH2O was lower (0.22±0.3 vs. 1.1±0.3L/day, p=0.0001). Conclusions: SCD is associated with important kidney dysfunction. The main abnormalities found were urinary concentrating and incomplete distal acidification defect. There was also an increase in the potassium transport and decrease in water reabsorption, evidencing the occurrence of distal tubular dysfunction.